(untitled) (Journal of Contemporary Philology, 2025)
This qualitative study investigated the translation techniques used to translate English COVID-19 neologisms into Kiswahili to suit the communicative needs of the general public. The data were collected from two websites which host health texts that are translated into many languages. From Medline Plus and Doctors of the World websites, a total of five English-Kiswahili translated COVID-19 texts were purposefully selected because they were the only available texts at the time of data collection. From these texts, a total of 18 COVID-19 related neologisms with their English-Kiswahili translations were obtained. The translation pairs containing the neologisms in both languages were extracted and analysed based on the framework of translation techniques proposed by Molina and Albir (2002). The findings show that borrowing, description, established equivalent, modulation, amplification, generalisation, literal translation and reduction techniques were used to adapt those medical terms to the general domains of use where they would be used and understood by the general lay public in the Tanzanian context.